Analisis Kinerja Keuangan PT. Sepatu Bata Indonesia Tbk dengan Menggunakan Metode Du Pont System Sebelum dan Selama Pandemi Covid-19 - Triandhini, Rekky; Kustiningsih, Nanik (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This study was conducted with the aim of being able to test whether there is a comparison of financial performance before the pandemic (2018-2019) and during the covid-19 pandemic (2020-2021) through the use of the Du Pont System approach at PT Sepatu Bata Indonesia Tbk. The indicators used include Net Profit Margin (NPM), Return on Asset (ROA), and leverage factors. These three indicators will determine the company's Return on Equity (ROE). From the test results, it is known that the financial performance of PT Sepatu Bata Indonesia Tbk from 2018 to 2021 analyzed using the Du Pont System is in a bad condition. The Covid-19 pandemic has had an impact on the company's financial performance, as seen from the declining Return on Equity (ROE) value. The results obtained from the research have shown that the value of Net Profit Margin (NPM), Return on Asset (ROA), Equity Multiplier, Return on Investment (ROI) and Return on Equity are quite influential before and during the pandemic.